Qaḍiyyat al-Waṭan fī Dīwān al-Tajawwul fī al-Mawāniʾ al-Baʿīdah li ʿĀrif Khuḍayrī wa Dīwān Damāʾ fī Santuḥan li Syukrī Zayn (Dirāsah Taḥlīliyyah Muqāranah) - Rahmah Ahmad H Osman (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2017)
This article tries to compare the issue of homeland in these two collections of poems entitled “at-Tajawwal fī al-Mawāniʾ al-Baʿīdah” by the Egyptian poet ʿArif Khudairiy and “Damai dalam Sentuhan” by Syukri Zeyn from Brunei Darussalam. Those two poets are chosen for comparative study in this research because of their backgrounds and impressions, such as the extensive cultural experience of ʿArif Khudairiy in the Malay countries, especially Brunei Darussalam and Malaysia, through which we can observe how the Malay environment affected his poetic works. As for Syukri Zeyn, he is regarded as the pioneer of modern Islamic poetry in Brunei Darussalam and possesses a strong Arabic linguistic and cultural background, having graduated from Al-Azhar University. However, the most important reason is the close relationship between the two poets. In this comparison, we have relied on the comparative descriptive analytical methodology. The methodology covers clarifying the issue of homeland in Arabic and Malay poetry, describing the backgrounds of the two poets and their collections of poems, and analyzing the issue of homeland according to each poet. It is followed by highlighting the similarities and differences in their treatment of the issue of homeland. The results show that there are similarities between the two poets in several aspects, such as the simplicity of the language used, the use of symbols and rhetorical imagery, and some of the places where the poems were written. The differences between the two poets can be seen in the purpose of their poems, the fluency of the language, and the number of stanzas and lines in their poems.